Strategi Pengembangan Subak Menjadi Lembaga Berorientasi Agribisnis di Kabupaten Badung (Kasus Subak Sengempel, Desa Bongkasa, Kecamatan Abiansemal) - BUDHIARTI, KADEK AYU RATNA; WINDIA, WAYAN; ASTITI, NI WAYAN SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.5, No.4, Oktober 2016, 2016)
Strategy of Subak Development into an Agribusiness-Oriented Institution in Badung Regency (The Case of Subak Sengempel, Bongkasa Village,Abiansemal District)   Agricultural development is done through an approach of agribusiness system which constitutes the whole subsystems of farming which are interrelated, interdependent and mutually influential. The aim of this study was to formulate strategies of Subak development into an agribusiness-oriented institution. This research was conducted in Subak Sengempel, Abiansemal District Badung regency. This study used 16 respondents (14 internal respondents and two external respondents) by means of purposive sampling. Data analysis method used was descriptive, qualitative, and quantitative method in order to obtain alternative strategies by using SWOT (strength, weakness, opportunity, threat). The results showed that Sengempel Subak position was in cell one, Growth position. This growth position stated that Subak Sengempel was currently experiencing growth. Based on the SWOT (strength, weakness, opportunity, threat) analysis, six alternative strategies can be recommended. The prioritized alternative strategy was the strategy of Subak development into an agribusiness-oriented institution. This Subak development into agribusiness-oriented institution was expected to become an independent and profit-oriented organization, able to survive and compete in the era of modernization. The recommended suggestion in this research is the development of Subak into an agribusiness-oriented institution is very possible with a real program. It can promote farmers’ independence, coordination with relevant parties, and create a pilot area of agribusiness that could be a motivation and foster the spirit of farmers in developing Subak into to an agribusiness-oriented institution.
Keywords: strategy; development; agribusiness